The sunset for the traditional Political Parties in Venezuela (2009)
This article seeks to show the changes and the political context in which the Venezuelan traditional political parties were eroded. The article begins with an historical overview identifying how the development of these political institutions created the conditions for the erosion of the parties as axes of political life in Venezuela. Analyzes the deterioration of the formula ADCOPEI and outlines the emergence of personalistic movements, the phenomenon “Chavez” as a consequence of the decline of organized forms of representation